Synthesis of Ternary Homogeneous Azeotropic Distillation Sequences: Entrainer Selection - Sutijan Sutijan; Megan Jobson; Robin Smith (ASEAN Journal of Chemical Engineering, 2012)
This paper presents a methodology for automatic selection of entrainers for separating binary azeotropic mixtures using homogeneous azeotropic distillation. A new classification system for ternary mixtures based on the termini of distillation boundaries and the type (stability) of products and azeotropes is proposed. The new characterisation system is able to link candidate entrainers to flowsheet structures which can facilitate the separation. Existing entrainer selection criteria are extended to accommodate other promising entrainers, including light, intermediate and heavy-boiling entrainers.